2016
DOI: 10.1097/hjh.0000000000000976
|View full text |Cite
|
Sign up to set email alerts
|

Reference values and associated factors for Japanese newborns’ blood pressure and pulse rate

Abstract: The present study is the first to show the distributions of Asian newborns' BP levels and pulse rate. The assessment of newborns' BP levels and pulse rate should consider birth weight, gestational age after birth, and actual condition at BP measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 48 publications
(92 reference statements)
0
11
0
1
Order By: Relevance
“…BP be most accurate in a quiet, resting infant and higher in those who are crying, however other activities such as feeding or even non-nutritive sucking may increase BP as well (figure 2). [51,52] Consistent measurement technique is essential to obtain accurate BP values. Standardized protocols for measurement of BP are available [53,54] and help to ensure that accurate BP values are obtained to guide clinical decision making.…”
Section: Clinical Presentation and Diagnostic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…BP be most accurate in a quiet, resting infant and higher in those who are crying, however other activities such as feeding or even non-nutritive sucking may increase BP as well (figure 2). [51,52] Consistent measurement technique is essential to obtain accurate BP values. Standardized protocols for measurement of BP are available [53,54] and help to ensure that accurate BP values are obtained to guide clinical decision making.…”
Section: Clinical Presentation and Diagnostic Evaluationmentioning
confidence: 99%
“…Figure 2.Effect of infant state on blood pressure (BP) (black bars, systolic BP; grey bars, diastolic BP). Data adapted from Satoh et al[52].…”
mentioning
confidence: 99%
“…Maternal hypertension, diabetes, use of illicit substances0–1Hospital: postnatal clinical, other in a non-clinical room406Oscill.P5xMean of three measurementsNormative BP during first year of life of healthy infantsKarmar et al [18]SwedenChildren, junior schoolPhysical health problems, medication that affects BP6–16Community setting1470Oscill.P5SexMean of second and third measurementCross-sectional normative casual BP standardsKrzyzaniak et al [19]PolandSchool childrenx7–18Community setting6447Auscul.P5Sex, heightMean of two measurements on three different daysTo develop age- and gender-specific reference rangesLurbe et al [20]SpainNormotensive childrenSystemic and renal disease6–16Primary care248Oscill.P5Sex, casual and ambulatory BPMean of three measurements and means of daytime measurementsAssess reference values of ambulatory blood pressureRosner et al [21]USA11 large paediatric blood pressure studies (based on Paediatric Task Force database) [22]Overweight1–17Unspecified36,914Auscul.P1, P5Sex, heightFirst measurementNorms for childhood BP among normal-weight childrenSarganas [23]GermanyHealthy children and adolescentsChronic conditions or medication influencing growth or BP. Overweight (BMI > 90th centile)3–17Community setting14,836Oscill.P1, P5Sex, heightMean of two measurementsFifth percentile of BP according to age, sex and heightSatoh et al [24]JapanFull-term singleton newbornsTwin newborns, miscellaneous abnormalities, missing Apgar score, condition during BP measurement0Hospital2628Oscill.P5SexFirst measurementEstimate BP and pulse rate in healthy newbornsSchwandt et al [25]GermanyGerman parentsMetabolic, cardiovascular, endocrine, malignant disorder, specific medication, non-German ethnicity3–18…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the previous studies, our study conducted an exhaustive systematic search for population-based centiles in all ages and compared them with a large sample of cut-offs for hypotension that are widely used in clinical practice. Our study identified only two studies that provided blood pressure centiles in children < 1 year including one study in new-borns and one at age of 6 months [17, 24]. Therefore, more studies providing reference values of blood pressure in children < 1 year are required.…”
Section: Discussionmentioning
confidence: 99%
“…( 201 Η μέτρηση της αρτηριακής πίεσης πρέπει να γίνετε σε ένα ήσυχο για 15 λεπτά και ξεκούραστο βρέφος σε ύπτια ή πρηνή θέση, 1.5 ώρα μετά την χορήγηση φαρμακευτικής αγωγής ή γεύματος χρησιμοποιώντας την κατάλληλη περιχειρίδα στο δεξιό βραχίονα με επαναλαμβανόμενες μετρήσεις. (245,246,247,248,249) Αντίθετα σε νεογνά που δεν έχουν σιτιστεί, είναι ανήσυχα και κλαίνε, μπορεί να οδηγηθούμε στην καταγραφή αυξημένων τιμών αρτηριακής πίεσης. (250).…”
Section: ιβ3 ορισμόςunclassified